Goal congruence in Brazilian organizations - Farris, George F.; Butterfield, D. Anthony (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A study of 189 professionals in 1 3 Brazilian financial institutions sought to apply U.S.-derived organization theory and methodology concerning congruence between individual and organizational goals. A substantial lack o f congruence was found, with congruence greater for higher organizational levels. Congruence was positively associated with involvement in work, and negatively associated with propensity to leave the organization. Relationships were stronger for some goals (e.g., self-actualization and status) than others (e.g., competent supervision and working on relevant problems ). Results of the study indicate that questionnaire methodology is suitable for studying professionals in Brazilian organizations, and that goal congruence theory holds in Brazil as it does in the U.S.